Japan in the World - Harootunian, Harry D., 1929-; Miyoshi, Masao (Book collections on Project MUSE., 1993)
Since the end of World War II, Japan has determinately remained outside the current of world events and uninvolved in the processes determining global history and politics. In Japan and the World, distinguished scholars, novelists, and intellectuals articulate how Japan-despite unprecedented economic prowess in securing dominance in the world's market-is caught in a complex dependency with the United States. Drawing on critical and postmodernist theory, this timely volume situates this dependency in a broader historical context and assesses Japan's current dealings in international politics.